HEALTH HAZARDS LINKED TO THE QUALITY OF THE IRRIGATION WATER AND TO THE CONSUMPTION OF THE VEGETABLES GROWN IN THE MARKET GARDENING SITE OF NKOLONDOM, (YAOUNDE - CAMEROON) - Hinson, Vikkey; Mbaduet, Yvonne; Djouaka, Rousseau; Zeukeng, Francis; Adjobimey, Menonli; Gounongbé, Fabien; Fayomi, Benjamin (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
Background: The water used for irrigation contains measurable quantities of dissolved substances which, when accumulated in the soil and crops, have serious consequences on the environment and human health. This cross-sectional and descriptive study was carried out on the Nkolondom vegetables production site in order to assess the health risks related to water used for irrigation and thus, improve on the quality of vegetables and the health of consumers.Methods: Thirty structured questionnaires were administered to vegetable producers. Water used for irrigation and the main vegetables produced were carefully collected to determine the degree of contamination in toxic heavy metals (Pb, Cd, As, Cu) and in microbes or fecal and total coliforms. A new advanced and sensitive approach, the Metalyser Pro HM3000 helped us to quantify the heavy metals.Results: Vegetable growing in Nkolondom is a basic activity which is characterised using traditional watering cans for irrigation, the non-use of personal protective equipment and the excessive use of inputs and pesticides. Irrigation is done with water from the river et the main crops produced there are lettuce and celery. The irrigation water as well as the vegetables that were analysed contained non-toxic doses of heavy metals which varied as follows:  Cu> Pb> As> Cd. The mean concentrations in fecal coliforms found were not toxic in the water used for irrigation (100 UFC/100 ml) and toxic in the vegetables (2,67 104 UFC/100 g). Vegetables grown in Nkolondom are thus dangerous for consumption and could cause many health issues to vegetable producers. Conclusion: The health risks are related to the environment, to the irrigation water, to the chemicals used, (pesticides and fertilisers) and to the physical workload. Vegetables producers mostly suffer from water-borne diseases, skin diseases and musculoskeletal disorders.